Designing a Sales Strategy with SWOT Method for Small and Medium Enterprises Products - Prima Vitasari; Lenny Herawati; Dayal Gustopo; Fuad Achmadi; Mazita Mokhtar (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This research was conducted on SMEs of brown sugar. This business has difficulty increasing sales especially in the new products from SMEs, namely printed brown sugar products. Where previously this SMEs only produced and sold bulk brown sugar. Design/methodology/approach: The methods used are Fishbone and Pareto, to identify the factors that can support the sales strategy. Findings: The results showed that there are internal factors and external factors as a sales strategy. Fishbone and Pareto diagram shows that internal factors have strength and weakness, indicating that there are SMEs that have their own business capital, workers who are experienced in making brown sugar. Meanwhile, external factors, in the form of opportunities and threats, where SMEs already have markets and customers. Research limitations/implications: Current condition has several obstacles, such as facing increasingly competitive competition, more types of products, rapid technological developments, and the number of similar businesses. This has an effect on conventionally run businesses such as SMEs. Practical implications: The results showed that there are internal factors and external factors as a sales strategy. Fishbone and Pareto diagram shows that internal factors have strength and weakness, indicating that there are SMEs that have their own business capital, workers who are experienced in making brown sugar. Meanwhile, external factors, in the form of opportunities and threats, where SMEs already have markets and customers. In the Threat factor, technology and competitors are found to be a threat, but if examined again, these two things are real opportunities for SMEs. The use of technology in this digital era can be used as a promotional medium, while the identified competitors come from outside the area of SME. These competitors can surely be a driver of good performance in running their business. Paper type: is categorized as a research paper